Recording cilia activity in ctenophores: effects of nitric oxide and low molecular weight transmitters - Norekian, Tigran P.; Moroz, Leonid L. (Frontiers in Neuroscience, 2023)
Cilia are the major effectors in Ctenophores, but very little is known about their transmitter control and integration. Here, we present a simple protocol to monitor and quantify cilia activity and provide evidence for polysynaptic control of cilia coordination in ctenophores. We also screened the effects of several classical bilaterian neurotransmitters (acetylcholine, dopamine, L-DOPA, serotonin, octopamine, histamine, gamma-aminobutyric acid (GABA), L-aspartate, L-glutamate, glycine), neuropeptide (FMRFamide), and nitric oxide (NO) on cilia beating in Pleurobrachia bachei and Bolinopsis infundibulum. NO and FMRFamide produced noticeable inhibitory effects on cilia activity, whereas other tested transmitters were ineffective. These findings further suggest that ctenophore-specific neuropeptides could be major candidates for signal molecules controlling cilia activity in representatives of this early-branching metazoan lineage.